Examination of the Psychometric Properties of the Spiritual Fitness Assessment - Kassab, Veronica A. (Journal of religion and health, 2011)
Using a sample of 196 undergraduate students, the present study investigated the psychometric properties of the Spiritual Fitness Assessment, a measure of spiritual fitness designed for use by health and fitness professionals. Examination of inter-item consistency produced satisfactory alpha coefficients for the total test and its three subscales. Correlations of the SFA with measures of spirituality and spiritual well-being provide support for convergent validity. Significant positive correlations with a measure of self-esteem suggest that the test has satisfactory criterion validity. Correlations with age, sex, and a measure of social desirability indicate that the SFA is significantly, though only moderately, affected by demographic variables and motivated response tendencies. Factor analysis of the SFA items indicate that the test is factorially complex and subscales may need to be refined to better measure their intended constructs. Overall, the results of the study suggest that the test may be useful for evaluations of spiritual fitness. Further research with samples drawn from different populations is needed on the test to better establish its reliability and validity.